The relationship between image building, trust and satisfaction with the policy of debt settlement from fundamental of education loans. - Meechao, Opad (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research objective to study the relationship between image building, trust and satisfaction of the policy of debt settlement from fundamental of education loans. The researcher collected 420 students from the Bangkok Metropolitan by quota sampling. The research found that creating the image of the education loan fundamental was related to trust in debt settlement policy 77%. , related to the satisfaction 66%, related trust 92% respectively. When analyzing the confirmatory factors, it was found that (1) Factor that affect the image building the first of three educational loan funds were: The image building of the loan fund for education It shows that people in the country give priority and opportunity to study (l = 50), Representing Corporate Social Responsibility (l = 47), the image of the loan fund for education Reflect the confidence of the people in the national pride focus on education for youth (l = 43) (2) Factors that affect trust in debt settlement policy with educational loan fund The first three are: Trust the reputation of the Educational Loan Fund (l = 56), Trust in value and the utility of being a member of the education loan fund (l = 55), Trust that the loan for you trust that education loan funds. It has fair allocation and gives equal access to education (l = 52). (3) The factors that affecting the satisfaction of the policy on repayment of the educational loan fund. The first three are: Settlement policies respond to beliefs and values (l = 64). Satisfaction (l = 57) and Feelings of good bond to education loan fund (l = 54). Article history : Received 22 March 2018 Revised 13 July 2018 Accepted 31 July 2018 SIMILARITY INDEX = 7.18